Pattern of childhood onset vitiligo at a tertiary care centre in south- west Rajasthan - Ashu Kayal; Lalit K Gupta; Ashok K Khare; Sharad Mehta; Asit Mittal; C M Kuldeep (Wolters Kluwer Medknow Publications, 2015)
Context : Onset of vitiligo during childhood is not uncommon but the data is limited on this subject. Aims : This study was planned to assess the magnitude of childhood onset vitiligo (COV) and adulthood onset vitiligo (AOV), and compare their clinical pattern. Settings and Design : A cross sectional hospital based clinical study. Materials and Methods : Consecutive patients with vitiligo attending the Dermatology OPD of RNT Medical College and MB Government Hospital, Udaipur, from April 2012 to September 2012 were the subjects of this study. A detailed history taking followed by general, systemic and cutaneous examination, and relevant investigations were carried out. The findings were recorded in a proforma for analysis and interpretation of data. Statistical analysis used : Statistical analysis of data was done using chi- square and Z test. Results: Of the 295 patients seen during the study period, 109 (36.95%) were patients with COV while 186 (63.05%) had AOV; the COV: AOV ratio being 1: 1.71. Amongst COV patients, females (65/109; 59.63%) outnumbered males (44/109; 40.37%). Maximum (51; 46.79%) patients of COV had onset of their disease on head and neck, out of which eyelid was the initial site of lesion in 29 (26.61%) patients. None of COV patients had universal and isolated mucosal vitiligo. Conclusions : Female predominance, affection of eyelids as initial site, and less frequent mucosal involvement in COV were the clinical features different from AOV.